Pedagogical Opportunities of the Reflective Learning Portfolio: Oportunidades pedagógicas del portafolio de aprendizaje reflexivo - Andresa Sartor-Harada; Oscar Ulloa-Guerra; Angel Deroncele-Acosta; María Elena Pérez-Ochoa (Revista de Filosofía, 2022)
The research analyses the pedagogical opportunities presented by the reflective learning portfolio as an educational tool. A case study is conducted where empirical findings are rationally reflected upon. It carries out a pretest-posttest design with a control group; applied to students from six countries who are taking virtual master’s degree programmes at a university in Mexico. The Honey-Alonso Questionnaire is used to measure effectiveness. The results show that, if the instrument is used transversally, covering the Master’s thesis, it is possible to encourage reflective learning. Moreover, there are no significant correlations between the gender and country of the trainees and the results. The evidence points to the advantages of using the portfolio as a promoter of critical thinking in e-learning environments, as it favours meta-reflection and dialogical collaboration between the actors in the training process, allowing the dynamisation of relevant learning of future graduates as global citizens.